Real-Time PCR Quantification and Diversity Analysis of the Functional Genes aprA and dsrA of Sulfate-Reducing Prokaryotes in Marine Sediments of the Peru Continental Margin and the Black Sea - Schippers, Axel; Blazejak, Anna (Frontiers in Microbiology, 2011)
A quantitative, real-time PCR (Q-PCR) assay for the functional gene adenosine 5´-phosphosulfate reductase (aprA) of sulfate-reducing bacteria (SRB) was designed. This assay was applied together with described Q-PCR assays for dissimilatory sulfite reductase (dsrA) and the 16S rRNA gene of total Bacteria to marine sediments from the Peru margin (0 – 121 meters below seafloor (mbsf)) and the Black Sea (0 – 6 mbsf). Clone libraries of aprA show that all isolated sequences originate from SRB showing a close relationship to aprA of characterised species or form a new cluster with only distant relation to aprA of isolated SRB. Below 40 mbsf no aprA genes could be amplified. This finding corresponds with results of the applied new Q-PCR assay for aprA. In contrast to the aprA the dsrA gene could be amplified up to sediment depths of 121 mbsf. Even in such an extreme environment a high diversity of this gene was detected. The 16S rRNA gene copy numbers of total Bacteria were much higher than those of the functional genes at all sediment depths and used to calculate the proportion of SRB to the total Bacteria. The aprA and dsrA copy numbers comprised in average 0.5 - 1 % of the 16S rRNA gene copy numbers of total Bacteria in the sediments up to a depth of ca. 40 mbsf. Depth profiles of the aprA and dsrA copy numbers were almost equal for all sites. Gene copy numbers decreased concomitantly with depth from around 108 / g sediment close to the sediment surface to less than 105 / g sediment at 5 mbsf. In the zone without detectable sulfate in the pore water from ca. 40 – 121 mbsf (Peru margin ODP site 1227), only dsrA (but not aprA) was detected with copy numbers of less than 104 / g sediment, comprising ca. 14 % of the 16S rRNA gene copy numbers of total Bacteria. In this zone sulfate might be provided for SRB by anaerobic sulfide oxidation.